Rapid detection of food adulterants and contaminants : theory and practice - Jha, Shyam N. (Academic Press, an Imprint of Elsevier, 2016)
Rapid Detection of Food Adulterants and Contaminants: Theory and Practice contains solid information on common adulterants and contaminants in various foods, guidelines for different standards, permissible limits prescribed by food regulatory authorities, and related detection techniques. This is an essential reference for anyone interested in progressive research on detection methods for food safety, especially researchers engaged in developing fast, reliable, and often nondestructive methods for the evaluation of food safety.
Keywords: Food adulteration and inspection.; Food contamination.; elektronické knihy; electronic books